2015
DOI: 10.2217/pgs.15.62
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in 6-Mercaptopurine Pathway as Potential Factors of Hematological Toxicity in Acute Lymphoblastic Leukemia Patients

Abstract: Genetic polymorphisms in enzymes and transporters involved in the 6-mercaptopurine pathway should be considered during its use to avoid hematological toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 38 publications
3
20
0
1
Order By: Relevance
“…More data on the relationship between ITPA genotype and ADRs of thiopurine drugs have been reported in the literature . Some studies concerning the paediatric population are available with only two studies on paediatric patients with immune disease (IBD) . In paediatric populations, a relation between ITPA genotype with hepatotoxicity was reported in some studies but not all .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More data on the relationship between ITPA genotype and ADRs of thiopurine drugs have been reported in the literature . Some studies concerning the paediatric population are available with only two studies on paediatric patients with immune disease (IBD) . In paediatric populations, a relation between ITPA genotype with hepatotoxicity was reported in some studies but not all .…”
Section: Discussionmentioning
confidence: 99%
“… reported a significant association between inosine triphosphatase IVS2+21A→C variants with thrombocytopenia, Hareedy et al . found significant associations between ITPA single‐nucleotide polymorphisms (SNPs) and haematological toxicity manifestations (neutropenia and leukopenia), Dorababu et al . reported that TPMT and ITPA genotypes together can explain 27% of the variability in haematological toxicity, and Azimi et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, considering there is an obligation to get both an informed consent and an informed assent, we believe this is a good starting number of subjects. In relation to that, there are several recent published studies with relatively small number of children (Roy Moulik et al, 2015 ; Amitai et al, 2016 ) and even more, with adults with ALL (Hareedy et al, 2015 ). Despite this, we truly believe our results are only a preliminary contribution regarding the ALL susceptibility of our Mexican pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…In previous years, there has been substantial development in understanding the chemotherapeutics mechanisms of pharmacogenetics and pharmacogenomics (1315). The cytotoxic effect of chemotherapeutics against tumor cells has significant associations with the expression of specific genes or gene polymorphisms.…”
Section: Discussionmentioning
confidence: 99%